Hubungan Disminore dengan Aktivitas Belajar pada Remaja Siswi Kelas X dan XI SMA N Rancakalong - Anggi Saputra; Umi Khasanah; Sri Hayati; Maidartati; Siska Susilawati (Jurnal Keperawatan BSI, 2021)
Primary dysmenorrhea is pain that is felt during menstruation without any abnormalities in the genital organs. Pain is felt before or at the same time as the onset of menstruation and also lasts for several hours. Those who experience primary dysmenorrhea during menstruation will limit their daily activities, especially activities in learning at school. A student who experiences primary dysmenorrhea will certainly feel disturbed in their learning activities, even this often makes them absent or unable to attend school. In addition, it can reduce the quality of life as well. The purpose of this study was to determine "The Relationship Between Primary Dysmenorrhea And Learning Activities In Class X And XI Teenagers Of SMAN Rancakalong, Sumedang Regency". This type of research is descriptive correlational with a cross-sectional approach. The sampling technique used in this study was total sampling. The sample in this study amounted to 72 respondents. Data collection techniques in this study using a questionnaire in the form of google form. The univariate analysis technique uses percentages and bivariate analysis uses non-parametric techniques, namely the Spearman rank test. The results showed that most of the Rancakalong high school students experienced moderate dysmenorrhea (61.1%) and their learning activities were disrupted (61.1%). The Relationship Between Primary Dysmenorrhea And Learning Activities In Class X And XI Teenagers Of SMAN Rancakalong, Sumedang Regency with a p-value of 0.006 means that there is a relationship between Primary Dysmenorrhea And Learning Activities In Adolescent Class X And XI Students Of SMAN Rancakalong, Sumedang Regency. Therefore, it is necessary to provide health education about primary dysmenorrhea to adolescents in schools.